Ultra Wide Band Dielectric Rod Antenna - I. D. Pavlov; Ya. V. Karaev; M. A. Kot (Известия высших учебных заведений России: Радиоэлектроника, 2020)
Introduction. Often, the space allocated for placement of an antenna has an inconvenient shape for this. The inconvenience is that its overall dimensions, namely the length and height, relate to each other approximately as 5:1. The task of placing the antenna in the space, in the absence of ready-made solutions, involves the development of an antenna with a similar ratio (5:1) of overall dimensions and with the possibility of convenient mounting on a flat conductive surface. Also, in the 9:1 frequency band, the antenna should have the following radio technical characteristics: voltage standing wave coefficient (VSWR) of not more than 3, gain of at least 1 dBi, radiation patterns should be axisymmetric with side lobe level not exceeding 25 %.Aim. Development and study of the characteristics of an ultra-wideband dielectric rod antenna.Materials and methods. Two structurally different versions of an ultra-wideband dielectric rod antenna were proposed. The main radio technical characteristics of both options were obtained through electrodynamic modeling in Ansoft HFSS.Results. As a result of the simulation, the following radio characteristics were obtained: – for the first option, the VSWR does not exceed 3.25 in the required frequency range, the gain varies from 6 to 12 dBi, the axisymmetric radiation patterns with the level of the side lobes not exceeding 30 %; – for the second option, the VSWR does not exceed 2.75 in the required frequency range, the gain varies from 5 to 11 dBi, the axisymmetric radiation patterns with the level of the side lobes not exceeding 20 %; In addition, the structural differences of the second option make it convenient to fix it on a flat conductive surface.Conclusion. Comparison of the obtained results with the requirements for the antenna under consideration shows that, unlike the first, the second option has an acceptable level of matching (VSWR 2.75) and of side radiation of radiation patterns (20 %). Based on this, it can be concluded that only the second option is suitable for the intended application.